ECONOMICS AND ETHICS (World Bulletin of Management and Law, 2022)
The study dealt with the concepts of economics and ethics and aimed to find out whether there is a relationship between them. We have systematically reviewed in detail the literature on ethics and economics separately and studies on both economics and ethics. Research questions were identified based on an observed problem; Then we followed several steps. Defining the problem showed the need to pay attention to the verification of the topic and from the in-depth study of these studies we came to the conclusion. Economists are able to understand and predict outcomes more effectively when they consider the role of moral beliefs and obligations. And linking economics with ethics helps to understand customer behavior. And earns the organization a strong business reputation, which helps it to survive, continuity and increase productivity. In addition, the integration of economics with ethics leads to social responsibility, which makes some organizations pay more attention to the environmental aspect